Application of Functional Variable Method for Heisenberg Ferromagnetic Spin Chain Equation - ALI TOZAR; Orkun Taşbozan; ALI KURT (Journal of Innovative Science and Engineering)
The Heisenberg spin chain concept is a fundamental and generic model that describes the exotic magnetic behavior of certain materials, such as ferromagnetism, antiferromagnetism, and ferrimagnetism under critical temperatures. The concept of spin chain is based on Coulomb interactions due to Pauli exclusion principle rather than dipole-dipole interactions in explaining the high energy observed in the Weiss molecular field. With certain improvements to the Hamiltonian proposed by Heisenberg, the model has became more sophisticated and used successfully in explaining many of the physical phenomena observed experimentally. This model has been extensively studied by physicists since the emergence of quantum physics at the beginning of the 20th century. Due to nonlinear interactions inherent in the model, soliton solutions that can be obtained have attracted the attention of mathematicians, in recent decades. In this study, triangular soliton, bell shaped solitary wave and kink shaped solitary wave solutions were obtained by applying the functional variable method to the nonlinear Heisenberg spin chain equation for a cubic lattice crystal.